Capital Will Not Become More Expensive as the World Ages - Bussolo, Maurizio (World Bank Group, Washington, DC, 2014)
Aging of populations and convergence between developed and developing countries in per capita incomes are shaping the evolution of saving, investment, capital flows, and, in particular, the cost of capital. When considering these trends, the existing literature argues for either continued, low interest rates, or sharply rising ones. This paper presents an alternative view: modest rises in interest rates, which result from a combination of increases in the global weight of high-saving developing economies (limiting declines in global saving), and decelerations in the rate of growth in developing countries (constraining upward pressure in global investment). For the majority of countries, slowing capital demand resulting from decelerating growth, coupled with structural changes that influence its attractiveness as a destination for capital, moderate increases in interest rates. Changes in key assumptions do not alter this view. More specifically, the small rise in interest rates persists even in a scenario where growth in developing countries decelerates more slowly, or when elasticities governing the behavior of saving and investment are varied.